COMPARISON OF DRYING PROCESS AND PRESERVATIVES ON DRYING KINETICS, TEXTURE AND ANTIOXIDANTS RETENTION IN MULBERRY FRUITS - M. K. Khattak; M. Hanif; M. Khan; M. Ramzan; Abdurab (Journal of Animal and Plant Sciences, 2019)
The objective of the study was to compare drying processes (open sun, Hot Air of Solar Collector and Micro wave) and preservatives (potassium meta bisulphate, Sodium benzoate and control) on drying kinetics, texture and antioxidants retention of three species (Morus alba, Morus nigra and Morus.  Morus laevigata) in the mulberries. Mulberries were pretreated with preservatives and subject to selected drying processes. Drying kinetics, texture and antioxidant retention were determined before and after each drying process. The results were analyzed using three factorial completely randomized design and means were compared at p = 0.05. The statistical analysis of the data showed that different drying process showed a significant (p < 0.05) Effect on drying kinetics, texture and antioxidant retention in mulberry fruits. Preservatives showed a significant effect on drying kinetics while it showed a nonsignificant effect on the texture and antioxidant retention. High moisture lost hr-1 (5.4%) was recorded in the microwave while minimum (1.8%) was recorded in open sun drying. Good textured dried mulberries with optimum hardness (313g) and stiffness (141g.mm-1) were found in hot air dried samples. Similarly, more antioxidants (52%) retained in samples dried with hot air followed by microwave (47%) while the minimum (41%) was recorded in open sun drying. It was concluded that hot air drying is the best drying process to get valuable dried quality mulberries with good texture and more antioxidants.
Keywords: Drying Process; Preservatives; Mulberries; Texture; Antioxidants